Effects of novel cellulase (Cel 906) and probiotic yeast fermentation on antioxidant and anti-inflammatory activities of vine tea (Ampelopsis grossedentata) - Xu, Jin; Hussain, Mubasher; Su, Wenfeng; Yao, Qian; Yang, Guandong; Zhong, Yu; Zhou, Lin; Huang, Xiaoting; Wang, Zhixiang; Gu, Quliang; Ren, Yifei; Li, He (Frontiers in Bioengineering and Biotechnology, 2022)
Vine tea (Ampelopsis grossedentata) is a plant resource with good nutritional and medicinal, and is widely consumed in China. This study aimed to develop a functional vine tea fermentation broth using microbial fermentation and cellulase degradation. First, the most suitable probiotics for vine tea fermentation were screened, and the fermentation conditions were optimized. Then, a new cellulase (Cel 906, MW076177) was added to evaluate the changes in the contents of effective substances and to study its efficacy. The results show that saccharomyces cerevisiae Y-401 was identified as the best strain, the optimal fermentation conditions were a time of 94.60 h, feeding concentration of 115.21 g/L, and temperature of about 34.97ºC. The vine tea fermentation broth has a strong inhibitory ability on 2,2'-azinobis3-ethylbenzothiazoline-6-sulfonic acid (ABTS) (99.73%), peroxyl (53.15%), superoxide anion radicals (84.13%), and 1,1-Diphenyl-2-trinitrophenylhydrazine (DPPH) (92.48%). It has a decent inhibitory impact on the cell viability, tyrosinase activity (32.25%), and melanin synthesis (63.52%) of B16-F10 melanoma cells induced by α-MSH. Inflammatory cell recruitment was reduced in a zebrafish inflammation model. Therefore, this vine tea fermented broth has strong antioxidant, anti-melanoma, and anti-inflammatory effects, and has healthcare potential as a probiotic tea.